Applied Marketing Research - Evans Martin; Moutinho Luiz (Allyn And Bacon, 1992)
This book provides interesting illustrations and examples of the different kinds of practical problems that are involved in the application of marketing research methodology as an aid to managerial decision making. Preface, The Marketing Research Process: Designs and Techniques, Primary Data Collection: Interview - Observation - Experimentation, Data Collection: Sampling and Sample Design, Problems and Cases, Marketing Research: Applications and Industry, Product Research: New Product Development, Price Research, Promotion Research, Industrial Marketing Research, The Marketing Research Industry and the Future, Clippings from the Press, Index.